Textbook of Contact Dermatitis - Rycroft, Richard J. G.; Menné, Torkil; Frosch, Peter J.; Lepoittevin, Jean-Pierre (Springer Berlin Heidelberg, 2001)
The third edition of the Textbook of Contact Dermatitis is the most thorough coverage yet of every conceivable aspect of the modern-day management of contact dermatitis. Both irritant and allergic contact dermatitis are covered fully and clearly, special emphasis being given to occupational and environmental aspects, in addition to prevention, diagnosis and treatment. The Textbook also covers epidemiology, the computerization of patch test data and patient information systems, non-invasive techniques for quantification of contact dermatitis, methods of skin testing other than patch testing, skin penetration, quantitative risk assessment, the histopathology and ultrastructure of both irritant and allergic contact dermatitis, subjective reactions and medicolegal aspects. The editors and contributing authors are all leading practitioners in the field. They have thoroughly revised the original chapters that were retained, while adding a number of completely new chapters. Their expertise has thus enabled the compilation of a comprehensive, yet approachable, updated text, supplemented by a large number of illustrations, mostly in full colour, many tables and a useful index. The book will help the reader gain a better understanding of the theoretical basis of the subject, greater competence in everyday practice, and increased awareness of areas in which more clinical and laboratory research remains needed
Keywords: Dermatology; Allergology; Allergy; Kontaktdermatitis